Phenethyl isothiocyanate suppresses the metastasis of ovarian cancer associated with the inhibition of CRM1-mediated nuclear export and mTOR-STAT3 pathway. Issue 1 (2nd January 2017) - Shao, Wen Yu; Yang, Yong Liang; Yan, Huan; Huang, Qian; Liu, Kai Jiang; Zhang, Shu
ABSTRACT: Epithelial ovarian cancer is prone to metastasizing at an early stage, but their mechanisms remain unclear. CRM1 is an important nuclear exportin and inhibitors targeting CRM1 has been explored as an anti-cancer strategy. In previous study, we observed that PEITC could combine with the hydrophobic pocket of CRM1. In this study, we focused on the effects of PEITC on EOC and its mechanisms. Results showed that IC50 values of PEITC on SKOV3 and HO8910 cell line were 42.14 μM and 37.29 μM, respectively. PEITC inhibits the migration and invasion of SKOV3 and HO8910 cells in vitro . Oral administration of 10 μmol PEITC suppressed the metastasis of EOC in a xenograft mouse model in vivo . PEITC treatment decreased the expressions of CRM1 and mTOR (cargo protein of CRM1) in EOC cell lines and in xenograft mouse tissues. Moreover, CRM1-mediated nuclear export was attenuated by PEITC, mTOR accumulated in nucleus, expressions of mTOR S2448 and downstream effectors STAT3 S727, MMP2 and MMP9 were decreased in a dose- and time-dependent manner. Furthermore, immunohistochemical analysis showed that CRM1 and mTOR were increased in EOC tissues compared with benign ovarian tumors, and related with advanced stage, type II EOC, positive peritoneal cytology and decreased overall survival. In addition, CRM1 was positively correlated with mTOR levels. In conclusion, our data demonstrated that PEITC suppresses the metastasis of EOC through inhibiting CRM1-mediated nuclear export, subsequently suppressing the mTOR-STAT3 pathway. Both CRM1 and mTOR were increased in EOC patients, providing a rationale for further clinical investigation of PEITC in EOC treatment.